lgl, pins and aPKC regulate neuroblast self-renewal versus differentiation. - Lee, C.Y.; Robinson, K.J.; Doe, C.Q. (Nature, 2006)
How a cell chooses to proliferate or to differentiate is an important issue in stem cell and cancer biology. Drosophila neuroblasts undergo self-renewal with every cell division, producing another neuroblast and a differentiating daughter cell, but the mechanisms controlling the self-renewal/differentiation decision are poorly understood. Here we tested whether cell polarity genes, known to regulate embryonic neuroblast asymmetric cell division, also regulate neuroblast self-renewal. Clonal analysis in larval brains showed that pins mutant neuroblasts rapidly fail to self-renew, whereas lethal giant larvae (lgl) mutant neuroblasts generate multiple neuroblasts. Notably, lgl pins double mutant neuroblasts all divide symmetrically to self-renew, filling the brain with neuroblasts at the expense of neurons. The lgl pins neuroblasts show ectopic cortical localization of atypical protein kinase C (aPKC), and a decrease in aPKC expression reduces neuroblast numbers, suggesting that aPKC promotes neuroblast self-renewal. In support of this hypothesis, neuroblast-specific overexpression of membrane-targeted aPKC, but not a kinase-dead version, induces ectopic neuroblast self-renewal. We conclude that cortical aPKC kinase activity is a potent inducer of neuroblast self-renewal.